Practice and Research of Floating Offshore Photovoltaic Intelligent Climate Early Warning Platform - Chengsheng ZHOU; Shidong FANG (南方能源建设)
[Objective] This paper aims to explore a novel floating offshore photovoltaic system that not only effectively collects marine solar energy but also performs intelligent climate early warning. [Method] By integrating offshore photovoltaic technology with intelligent meteorological monitoring technology, we developed a viable intelligent offshore photovoltaic climate early warning platform. Firstly, the floating offshore photovoltaic platform was used to convert solar energy into electrical energy. Secondly, the intelligent monitoring system monitored ocean weather conditions in real-time and gave early warnings to improve the reliability of photovoltaic power generation. [Result] Tests show that the floating offshore photovoltaic system can effectively collect solar energy under different sea areas and weather conditions, and the intelligent meteorological monitoring system is used to timely give early warnings on the changes in marine meteorology. [Conclusion] This study finds that the platform has broad application prospects and market potential. It can provide references for the development of marine renewable energy and provide ideas and methods for related research and practice.